Elevation in Serum Concentration of Bone-Specific Alkaline Phosphatase without Elevation in Serum Creatinine Concentration Secondary to Adefovir Dipivoxil Therapy in Chronic Hepatitis B Virus Infection - Abe, Hiroshi (Hindawi Publishing Corporation, 2013)
Of 168 patients with chronic hepatitis B virus (HBV) infection-related liver disease, 20 patients who had received 100 mg of lamivudine plus 10 mg/day of adefovir dipivoxil (ADV) (ADV group) and 124 patients who had received 0.5 mg/day of entecavir or 100 mg/day of lamivudine (non-ADV group) for >1 year were enrolled. For comparative analyses, 19 well-matched pairs were obtained from the groups by propensity scores. At the time of enrollment, serum creatinine and phosphate concentrations were similar between the ADV and non-ADV groups; however, urinary phosphate (P = 0.0424) and serum bone-specific alkaline phosphatase (BAP) (P = 0.0228) concentrations were significantly higher in the ADV group than in the non-ADV group. Serum BAP was significantly higher at the time of enrollment than before ADV administration in the ADV group (P = 0.0001), although there was no significant change in serum BAP concentration in the non-ADV group. There was a significant positive correlation between the period of ADV therapy and ΔBAP (R (2) = 0.2959, P = 0.0160). Serum BAP concentration increased before increase in serum creatinine concentration and was useful for early detection of adverse events and for developing adequate measures for continuing ADV for chronic HBV infection-related liver disease.